Performance analysis of MIMO DUCA multiple antenna system - Gen-fu SHAO; Ying-li YAO; Jie ZHOU; Kikuchi HISAKAZU (Tongxin xuebao)
A MIMO multi-antenna system of compact double uniform circular array (DUCA) in three dimensional direc-tional frequency non-selective Rayleigh fading channel was analyzed and investigated. Equivalent network model of MIMO multi-antenna array considering MC effect was established, general expressions of correlations were derived and the relationship between correlations with and without MC was classfied. Then, the results were compared with general uniform linear array (ULA) and uniform circular array (UCA). It was concluded that the deployment of antennas plays a decisive role in correlations between antennas. The research has a good sense on designation of spatial massive MIMO multi-antenna array and system optimization.